Mosquito repellents: An insight into the chronological perspectives and novel discoveries - Islam, Johirul; Zaman, Kamaruz; Duarah, Sanjukta; Raju, Pakalapati Srinivas; Chattopadhyay, Pronobesh (Acta tropica, 2017)
•We have prepared an extensive review on mosquito repellents with special emphasize on novel discoveries with insect repelling properties.•The novel insect repellents demonstrated promising insect repellent activity.•These newly discovered insect repellents will pave the way in the development of safer and better alternatives of existing mosquito repellents. Mosquito being the major medically important arthropod vector; requires utmost attention to reduce the sufferings and economic consequences of those living in the endemic regions. This is only possible by minimising the human-mosquito contact by an absolute preventing measure. However, unfortunately, such absolute measures are yet to be developed despite enormous efforts and huge investments worldwide. In the absence of vaccines for number of mosquito-borne diseases, repellents could be an attractive option for both military personal and civilians to minimise the risk of contacting different mosquito-borne diseases. However, to achieve this golden goal, the detailed knowledge of a particular repellent is must, including its mode of repellency and other relevant informations. Here, in the present article, an effort has been made to convey the best and latest information on repellents in order to enhance the knowledge of scientific community. The review offers an overview on mosquito repellents, the novel discoveries, and areas in need of attention such as novel repellent formulations and their future prospective.